High-resolution analysis of silica and sulphate-rich rock varnishes from Victoria Land (Antarctica) - GIORGETTI G; BARONI, CARLO (European Journal of Mineralogy, 2007)
Rock varnishes on subaerially exposed surfaces of magmatic rocks in northern Victoria Land (Antarctica) have been analyzed using XRD, SEM-EDS and TEM-AEM techniques. The varnishes are tens of micron in thickness and consist of laminae with different chemical compositions. They always show sharp contacts with the underlying rocks. X-ray microanalysis enables two components to be recognized from their chemical compositions: a component rich in Si with minor Al, Fe, and Mg, and a S and Fe-rich component with minor Al, K, and P. Results of XRD and TEM work reveal that the Si-rich component is made of amorphous material containing few nanometer-thick smectite crystals, most of which have formed in situ. The S-rich component forms subrounded areas and laminae oriented parallel to the outer surface of the rock substrate and may be amorphous or crystalline. The crystals are sulphates of the alunite-jarosite series. The varnish is inferred to have formed by accretion onto the external surface of the rock substrate of airborne dust, followed by remobilization of some constituent and subsequent crystallization of clays and sulphates. The sulphur may have been derived from marine spray and/or fallout of active volcanoes.